Pijat I Love You (ILU) Solusi Asuhan Kebidanan dalam Mengatasi Bayi Kembung - Zulhendri, Annisa Fitri Nadillah; Lita Nafratilova (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The need for continuous midwifery care (Continuity of Care) is crucial given the high maternal and infant mortality rates that still frequently occur. One common problem in neonates is flatulence, which can cause discomfort to the baby and anxiety to parents. One non-pharmacological treatment that has been proven effective for flatulence in infants is the